A dietary supplement containing Raspberry, L-Carnitine, soy protein isolate, garcinia extract, Cactus extract and chromium (III) picolinate causes liver damages in rats: An acute toxicity test - Chanenath Sriaporn (2018)
© 2017, Chiang Mai University. All rights reserved. Many advertisements about one dietary supplement have been propagated more frequent during the past few years and claimed that it can block surplus carbohydrate and fat and also burn calories without any hazardous effect. In order to assure its safety, the acute toxicity test was conducted in Wistar rats by the single oral administration. Rats were divided into three groups. Group I was administered with 1 ml distilled water and served as control. Group II and III were administered at a dose of 1000 mg/kg body weight and 2000 mg/kg body weight, respectively. After 14 days, the rats were given euthanasia. Heart, liver and kidneys were weighted and subjected to histological examination. Blood samples were collected from cardiac puncture for complete blood count. The percentage of weight changes and relative organs’ weights in all groups showed no statistically significant differences (p > 0.05). Histologically, the deterioration of hepatocytes, blood congestion in the central vein and hepatic sinusoids, hemorrhages, abnormal vacuoles and focal necrosis were observed in treated groups. The complete blood count in female subjects from group III showed statistically significant differences in TRBC (p=0.013), MCV (p=0.016) and neutrophil (p=0.041).